2017
DOI: 10.1007/s40487-017-0040-8
|View full text |Cite
|
Sign up to set email alerts
|

Switching from an LHRH Antagonist to an LHRH Agonist: A Case Report of 10 Finnish Patients with Advanced Prostate Cancer

Abstract: IntroductionLuteinizing hormone-releasing hormone (LHRH) analogues are widely used for the treatment of advanced hormone-dependent prostate cancer. However, there are currently no clinical guidelines for switching between LHRH analogues. It has been reported that there may be clinical benefits for patients switching between different formulations of LHRH agonists, as well as from an LHRH agonist to LHRH antagonist, but there are no published data on switching from an LHRH antagonist to an LHRH agonist. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…All patients who switched to the leuprorelin acetate implant in the adjuvant setting stated that they preferred to continue with this therapy. 41 Although further data are needed to support these preliminary findings in Croatia and Finland, they are in line with the EAU 2016 guidelines statement that LHRH agonists demonstrate similar efficacy but that variations in practical aspects need to be considered in everyday practice. 1…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…All patients who switched to the leuprorelin acetate implant in the adjuvant setting stated that they preferred to continue with this therapy. 41 Although further data are needed to support these preliminary findings in Croatia and Finland, they are in line with the EAU 2016 guidelines statement that LHRH agonists demonstrate similar efficacy but that variations in practical aspects need to be considered in everyday practice. 1…”
Section: Introductionsupporting
confidence: 63%
“…PSA levels measured before and after switching from an LHRH antagonist to an LHRH agonist: a Finnish case series. 41 LHRH, luteinizing hormone-releasing hormone; PSA, prostate-specific antigen. Reproduced under the Creative Commons Attribution-noncommercial 4.0 license (http://creativecommons.org/licenses/bync/4.0/) with permission, from Visapää H. Switching from a luteinising hormone-releasing hormone (LHRH) antagonist to a LHRH agonist: a report of 10 Finnish patients with advanced prostate cancer.…”
Section: A Pharmacist's Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…For patients whose PSA levels are more than 20 ng/mL, GnRH antagonist treatment prolonged overall survival in comparison to GnRH agonist treatment [3]. Harri et al reported a case series in which GnRH agonists and antagonists were switched in Finnish prostate cancer patients [8]. The detailed mechanisms are still unknown; however, one possibility is that GnRH antagonists also lower the serum FSH level and that this decrease in FSH might be associated with an anti-tumor effect in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%